The Effects of DPP-4 Inhibitors, GLP-1RAs, and SGLT-2/1 Inhibitors on Heart Failure Outcomes in Diabetic Patients With and Without Heart Failure History: Insights From CVOTs and Drug Mechanism - Pan, Xiaohui; Xu, Shishi; Li, Juan; Tong, Nanwei (Frontiers in Endocrinology, 2020)
Patients with type 2 diabetes (T2D) have a higher risk of heart failure (HF) than healthy people, and the prognosis of patients with diabetes and current or previous HF is worse than that of patients with only diabetes. We reviewed the HF outcomes in recently published cardiovascular outcome trials (CVOTs) of three new classes of anti-diabetic agents, namely dipeptidyl peptidase-4 inhibitors (DPP-4is), glucagon-like-peptide 1 receptor agonists (GLP-1RAs), and sodium glucose cotransporter-2 inhibitors (SGLT-2is) or SGLT-2 and SGLT-1 dual inhibitors and divided the patients into two groups based on the history of HF (with or without) and analyzed their risks of HHF based on the receipt of the aforementioned anti-diabetes drug types. Since the follow-up period differed among the trials, we expressed the rate of HHF as events/1000 person-years to describe the HF outcome. At last we pooled the data and analyzed their different effects and mechanisms on heart failure outcomes. Although DPP-4is did not increase the risk of HHF in T2D patients with a history of HF, they were associated with a significantly higher risk of HHF among patients without history of HF. Some GLP-1RAs reduced the risk of macrovascular events, but none of these drugs reduced the risk of HHF in patients with T2D irrespective of their HF history. It was not clarified whether SGLT-1/2is can improve the prognosis of macrovascular events in patients with T2D, but these drugs reduced the risk of HHF regardless of patients’ histories of HF. This information may be useful or referential for the “precise” selection of hyperglycemic medications. Further researches still needed to clarify the mechanisms of these anti-diabetic medications.